Isolasi Proses Bioaktif Ekstrak Metanol Daun Putat (Planchonia valida) sebagai Antioksidan - Farid, Faizar; Br Sembiring, Vera Lorensya; Nelson, Nelson; Saputra, Muhammad Furqon Novryan; Putri, Silvi Ayudiah; Tarigan, Indra Lasmana; Latief, Madyawati (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2022)
Putat leaves (Planchonia valida) are a plant that is traditionally used by people in the Tanjung Lanjut areas, Jambi as fresh vegetables, and as a traditional medicine to treat skin diseases and restore health. This identifies that the putat plant contains chemical compounds that have the potential to have antioxidant activity. Extraction was carried out using n-hexane and ethyl acetate solvents using multistage maceration. Next, phytochemical screening and antioxidant activity tests are carried out to obtain information about fractions that can potentially proceed to the isolation stage. In the maceration process, an extract percentage was obtained with a yield value of 1.39%. Next, isolation was carried out using vacuum liquid chromatography. The isolates obtained were then characterized using UV-Vis and FT-IR spectrophotometer instruments. The isolate obtained was in the form of a wet solid, and if seen through characterization, it belonged to the class of steroid compounds; it was suspected to be an ergosterol compound. Antioxidants are known to have the ability to inhibit and reduce the presence of free radicals in the human body. In this study, antioxidant activity was tested using the DPPH (2,2-diphenyl-1-picrihidazil) method on F1 isolates. The F1 isolate obtained was proven to have antioxidant activity with a value of 99.2265 ppm, which is classified in the strong antioxidant activity range.